2016
DOI: 10.14740/wjnu249w
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Leiomyoma With Bizarre Nuclei: A Case Report

Abstract: Leiomyoma with bizarre nuclei (LM-BN) is a very rare finding which cannot be distinguished clinically from the very commonly occurring benign prostatic hyperplasia (BPH). If correctly diagnosed, LM-BN has a favorable prognosis after complete surgical excision. It is important to keep this alternative diagnosis in mind when treating a patient with complaints indicating prostatic hyperplasia. This case involves a 77-year-old male presenting with lower urinary tract symptoms; based on clinical presentation, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In 2016, Kristensen et al stated that prostatic leiomyomas were reported in <100 cases since it was defined. 1 Chronic inflammation and infectious pathogens were suggested to be responsible for leiomyoma pathogenesis. In addition, the origin of prostatic leiomyoma may reveal as wastes of Müllerian duct.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Kristensen et al stated that prostatic leiomyomas were reported in <100 cases since it was defined. 1 Chronic inflammation and infectious pathogens were suggested to be responsible for leiomyoma pathogenesis. In addition, the origin of prostatic leiomyoma may reveal as wastes of Müllerian duct.…”
Section: Discussionmentioning
confidence: 99%